Small-Scale Sport Events as Place Branding Platforms: A Content Analysis of Osona’s Projected Destination Image through Event-Related Pictures on Instagram - Isaac Taberner (MDPI AG, 2021)
Over the last few decades, various regions have taken advantage of sport as a tool for place branding. One of the most used strategies has been sporting events, which can help to position the regions and improve their image. With regard to destination image (DI), the penetration and popularity of social media such as Instagram has opened new avenues for place promotion and has turned the users of these platforms into active agents in the promotion of DI. This study aims to explore whether the participants and organisers of small-scale sport events (SSSEs) can contribute to the creation of destination image through the content they post on Instagram. For this purpose, the content of 1315 photographs posted by SSSE participants and organisers on Instagram was analysed. The results show that the photographs related to SSSEs reproduce destination attributes of the region and, consequently, are a source of DI creation. The results also show the importance of the specific moment of the event both in the DI and in the engagement of the posts. This research provides valuable information on the management of Instagram in the context of SSSEs, on the importance of the characteristics of the starting and finishing lines and of the course of the event; and on the desirability of aligning the perspective of the organisers and participants to maximise the potential for the creation of DI through SSSEs.